Progressive Muscle Relaxation (PMR) terhadap Tingkat Fatigue (Kelelahan) pada Pasien Chronic Kidney Disease (CKD) yang Melakukan Hemodialisa - Wisudayanti, Made Yoni; Heri, Mochamad; Putra, G. Nur Widya; Sugiartini, Desak Ketut; Wijaya, Gede Agus Sastra (Journal of Telenursing (JOTING), 2023)
This study aims to determine the effect of Progressive Muscle Relaxation (PMR) on the level of Fatigue (tiredness) in Chronic Kidney Disease (CKD) patients who carry out Hemodialysis at the Hemodialysis Unit at Wangaya Hospital, Denpasar. The method used in this study is a case study with a total sample of 1 patient who identified nursing care problems with complaints of fatigue who underwent hemodialysis. The results of this study are that the intervention given is in accordance with the diagnosis, namely active and passive movement exercises according to the Progressive Muscle Relaxation SOP. After the client is given progressive muscle relaxation, they feel less tired than before and feel more relaxed. This shows that progressive muscle relaxation therapy is effective for CKD sufferers who are undergoing hemodialysis. The conclusions from the results of this study are based on the analysis of the therapy giving progressive muscle relaxation effectively to relieve fatigue in patients undergoing hemodialysis, so that patients appear more relaxed and complain of fatigue reduced. Keywords: Chronic Kidney Disease (CKD), Fatigue, Progressive Muscle Relaxation (PMR)